Reproductive rate of a top predator, the grey seal, as an indicator of the changes in the Baltic food web - Kauhala, Kaarina; Korpinen, Samuli; Lehtiniemi, Maiju; Raitaniemi, Jari (Ecological Indicators, 2022)
Reproductive rate of grey seal (Halichoerus grypus) females has fluctuated during the 2000s, although reproductive disturbances, which occurred earlier, are rare at present. Here we aimed to study especially the food web factors possibly affecting the birth rate of Baltic grey seals and whether birth rate can be used as an indicator of the changes in the Baltic food web. Our results showed that the birth rate of grey seals was significantly related to herring (Clupea harengus membras) and sprat (Sprattus sprattus) quality (weight) which, in turn were influenced by sprat and cod (Gadus morhua) abundance, as well as zooplankton biomass and plankter size. This suggests strong trophic coupling over three trophic levels. We thus conclude that the birth rate of grey seals can be used as an indicator of the status of the Baltic food web. Based on this, we suggest a threshold value for good food web status for a stable, non-growing seal population. Highlights • Birth rate of grey seals was related to changes in the quality of clupeids. • The quality of clupeids reflected changes in the Baltic food web. • Birth rate can thus be used as an indicator of the status of the Baltic food web. • Different threshold values of birth rate for a growing and stable seal population should be determined.